Rabies in America during the Spanish dominion, 16th to 18th centuries - Paniagua Pérez, Jesús (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Rabies, historically called hydrophobia, is a type of zoonosis caused by Lyssavirus, of the Rhabdoviridae family.  It is an infectious disease that has caused concern since ancient times, due to the fear that it has produced, and which did not cease despite the discovery of a vaccine in 1885. The main objective of this article is the study of this disease in the context of Hispanic America, with its contrasts with respect to the European world, in its origin and development, as well as its medical and superstitious solutions. Therefore, it is of interest, in addition to the manifestations of the disease, the social and cultural aspects that it generated, including, in reference to criollismo, the promotion of purely American remedies. Consequently, a selective bibliography was used and American and Spanish libraries, newspaper libraries and archives were consulted from which were obtained the necessary materials to reach some conclusions that nuance what has already been stated, especially by experimental scientists, paying attention to the influence that the disease had, not only on the individual, but also on the society around them, and on the powers of the state, which was forced to make decisions in accordance with the problem.